Persepsi Kesehatan Dan Status Kesehatan Mental Penderita Rematik Di Ambon - Raatburu, Elda Janty; Ranimpi, Yulius Yusak; Soegiono, Simon Pieter (Jurnal Keperawatan Muhammadiyah, 2020)
Abstract Background: Health Department data shows an increasing amount of prevalence of rheumatic diseases significantly in Maluku Province, starting from the year 2012 there are 8,549 cases, in 2013 as many as 12,761 cases, and in 2014 there were 28,279 cases. These figures certainly show a decline in health status especially when the disease can have an impact on the physical health of the individual Objective: know the perception of health and mental health status of patients with rheumatoid arthritis in Ambon. Method: qualitative with phenomenology approach using purposive sampling technique. Data collection with structured interviews and using interview guides as a data gathering tool, as well as a validity test using source triangulation. Results: there are four major themes: healthy-sick perception, participant health status, mental health status including self-concept, emotional and cognitive aspects, and pain management patterns in cultural view. Conclusion: rheumatic sufferers perceive the healthy that can move and socialize, while the pain is when not able to move. Participants' mental health is not affected by the pain they experience, and when they get sick, participants take their own medication. Keywords: Mental Health, Perception, Rheumatism